2014
DOI: 10.1021/am500883q
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous and Sensitive Detection of microRNA with Ligase Chain Reaction and Lambda Exonuclease-Assisted Cationic Conjugated Polymer Biosensing

Abstract: A simple and homogeneous microRNA assay is developed by integration of ligase chain reaction (LCR) and lambda exonuclease-assisted cationic conjugated polymer (CCP) biosensing. LCR is utilized for exponential amplification of microRNA, and lambda exonuclease is introduced to degrade excess fluorescein-labeled probes in LCR for eliminating background signal. After addition of CCP, efficient fluorescence resonance energy transfer from CCP to fluorescein in LCR products occurs. The method is sensitive enough to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 29 publications
0
35
0
1
Order By: Relevance
“…Increasing evidence has indicated that abnormal expressions of specific miRNAs show close correlation to many important diseases, including human cancers and other diseases, and these specific miRNAs can be considered to be effective biomarkers for the diagnosis of different diseases. Because of the clinical significance of miRNAs, a series of bulk measurements have been developed to detect specific miRNA levels following isolation from cells, including traditional northern blotting, reverse transcription quantitative PCR (RT‐qPCR), and microarrays with modern fluorescent and electrochemical techniques . However, detection of the average miRNA expression in cell populations could lead to the loss of important information connecting miRNA expression with cell function.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing evidence has indicated that abnormal expressions of specific miRNAs show close correlation to many important diseases, including human cancers and other diseases, and these specific miRNAs can be considered to be effective biomarkers for the diagnosis of different diseases. Because of the clinical significance of miRNAs, a series of bulk measurements have been developed to detect specific miRNA levels following isolation from cells, including traditional northern blotting, reverse transcription quantitative PCR (RT‐qPCR), and microarrays with modern fluorescent and electrochemical techniques . However, detection of the average miRNA expression in cell populations could lead to the loss of important information connecting miRNA expression with cell function.…”
Section: Methodsmentioning
confidence: 99%
“…Primers termini also contained donor and acceptor dyes to enable FRET once brought into close proximity through the formation of a molecular beacon [108]. Yuan et al developed an integrated LCR-lambda exonuclease-assisted cationic conjugated polymer (CCP) biosensor for miRNA genotyping [109]. The ability of CCPs to harvest and amplify signal was used as a donor in the FRET transfer to fluorophore.…”
Section: Fluorescence Resonance Energy Transfer (Fret)mentioning
confidence: 99%
“…LCR is employed for two pairs of oligonucleotide probes which are adjacent and perfectly complementary to target miRNA or the ligated DNA strand for performing ligation-based exponential amplification [44]. Upon hybridization to a target miRNA strand, the adjacent probes are ligated by a specific ligase [45] (e.g., T4 RNA ligase 2 [46]) to form a long DNA strand.…”
Section: Lcrmentioning
confidence: 99%
“…With a LCR utilized for exponential amplification of miRNA and lambda exonuclease-assisted cationic conjugated polymer (CCP) for fluorescent signal detection, a homogeneous and sensitive detection of miRNA has been proposed ( Fig. 5.10) [44]. The method is sensitive enough to detect 0.1 fM target miRNA and specific to discriminate a one-base difference of miRNAs.…”
Section: Lcrmentioning
confidence: 99%